A mixed cation chiral perovskite nanosheet and preparation method thereof

Synthesis of mixed cationic chiral perovskite nanosheets through the dual ligand-assisted co-sealing method has solved the problem of weak circular dichromatic signals of existing chiral perovskite materials, and achieved the improvement of high CD value and anisotropic factors. Suitable for applications in a variety of optical devices.

CN115181565BActive Publication Date: 2024-12-27WENZHOU UNIV

Patent Information

Application Number
CN202210708526.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-21
Publication Date
2024-12-27
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

The circular dichromatic signal of existing chiral perovskite materials is weak, and the anisotropy factor gabs is close to zero, resulting in insufficient performance in applications such as circular polarization photodetectors, circular polarization light emitting diodes, three-dimensional displays, biological imaging, quantum computing, etc. .

Method used

Using the biligand-assisted co-precipitation method, the chiral organic ammonium, achiral organic ammonium and lead halide are used as precursors, and N,N'-dimethylformamide is used as solvent and toluene is used as anti-solvent to synthesize mixed cationic handrails. , the halogen atoms at the X position of the two-dimensional perovskite, improve their chiral activity and circular dichromatic signal.

Benefits of technology

A mixed cationic chiral perovskite nanosheet with high CD value and anisotropy factor gabs = -3.8×10-3 was obtained. The circular dichromatic signal is strong, the wavelength is adjustable, and the stability is good. It is suitable for high-performance chirality. Design and application of optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115181565B_ABST
    Figure CN115181565B_ABST
Patent Text Reader

Abstract

The invention discloses a mixed cation chiral perovskite nanosheet and a preparation method thereof, wherein the preparation method comprises the following steps: S1: using chiral organic ammonium, achiral organic ammonium and lead halide as perovskite precursors, organic small molecules as surface ligands, and N,N'-dimethylformamide as solvent to form a precursor solution; S2: using toluene as an anti-solvent, adding the precursor solution prepared in step S1 to the anti-solvent to synthesize a mixed cation chiral perovskite nanosheet. The synthesis method of the invention is simple and fast, and the obtained chiral perovskite nanosheet has a strong circular dichroism signal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic-inorganic hybrid perovskite materials, in particular to a mixed cation chiral perovskite nanosheet and a preparation method thereof. Background Art

[0002] Chirality, the inability of an object to coincide with its mirror image, is a fundamental property that exists not only in nature but also in art, chemistry, architecture and life. Chiral materials and their mirror images are called enantiomers or antipodes due to their noncentrosymmetric structures, and these materials exhibit interesting physical properties such as circular dichroism (CD), circularly polarized photoluminescence (CPL), nonlinear optical (NLO) effects, ferroelectricity, spintronics and bulk photovoltaic effects.

[0003] Halide perovskites have proven to be a promising class of optoelectronic materials for a variety of applications, including light-emitting diodes (LEDs), photonic lasers, photodetectors, and solar cells. Metal halide perovskite materials have valuable properties, including flexible crystal structure, long charge carrier diffusion length, high dielectric constant, highly tunable band gap, high optical absorption coefficient, and strong spin-orbit coupling, making them extremely promising materials. However, their chemical structures are always centrosymmetric. Therefore, chirality cannot be naturally generated in metal halide perovskites, and chiral molecules cannot be directly applied to relevant optical applications. Research in recent years has shown that chirality can be transferred from chiral organic molecules to halide perovskites, resulting in a new concept of chiral perovskite materials. The resulting chiral perovskites combine the advantages of chiral materials and halide perovskites, taking a huge step forward in the development of smart optoelectronic and spintronic materials and devices.

[0004] Chiral perovskites absorb right-handed and left-handed CPL differently, so they are potential materials for CPL detection. CPL detection has been widely used in various fields such as optical communications, quantum computing, medical diagnosis and image processing. In addition, the circularly polarized fluorescence spectrum of chiral perovskites can capture the excited state information of chiral structures. It has a wide range of applications in 3D display, optical security, information storage, biological probes and photocatalytic asymmetric synthesis. In addition, chiral perovskites are also widely used in circularly polarized photodetectors, ferroelectrics, nonlinear optical effects and white light LEDs. In order to better realize these applications, it is necessary to improve the chiral optical properties (such as CD value and anisotropy factor g) of chiral perovskites. abs ) is urgent.

[0005] Many papers (J.Phys.Chem.Lett.2021,12,2676; Adv.Mater.2021,2008785) have reported that the circular dichroism signal of chiral perovskite synthesized by ligand-assisted co-precipitation (LARP) with chiral ligand R- / S-MBABr as A-site ion is very weak, and its anisotropy factor g abs The reason may be that the crystallinity is too poor, resulting in the CD signal being almost 0. Therefore, it is of great significance to improve its crystallinity and CD signal so that it can be better applied to circularly polarized photodetectors, circularly polarized light-emitting diodes, three-dimensional displays, bioimaging, quantum computing, quantum communications, memory and spin transistors. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a high CD value, anisotropy factor g abs Mixed cation chiral perovskite nanosheets and their preparation method. This method provides a new strategy for the design of chiral optical properties of chiral perovskites.

[0007] The first aspect of the present invention is to provide a method for preparing a mixed cation chiral perovskite nanosheet, comprising the following steps:

[0008] S1: Chiral organic ammonium, achiral organic ammonium and lead halide are used as perovskite precursors, small organic molecules are used as surface ligands, and N,N'-dimethylformamide is used as solvent to form a precursor solution;

[0009] S2: Using toluene as an anti-solvent, the precursor solution prepared in step S1 is added to the anti-solvent to synthesize mixed cation chiral perovskite nanosheets.

[0010] It is further arranged that the chiral organic ammonium is any one of R- / S-methylbenzylammonium bromide, R- / S-methylphenethylammonium bromide, R- / SN-methylphenethylammonium bromide and R- / S-methylbenzylammonium iodide.

[0011] It is further arranged that the achiral organic ammonium in step S1 is any one of phenethylammonium bromide or phenethylammonium iodide.

[0012] It is further provided that the lead halide in step S1 is PbBr 2 or PbI 2 .

[0013] A further setting is that the total amount of the mixed ammonium salts in step S1 should remain unchanged, such as 0.08 mmol.

[0014] It is further provided that the total amount of the mixed lead salts in step S1 should remain unchanged, such as 0.04 mmol.

[0015] It is further configured that the molar ratio of the mixed organic ammonium cation and the lead halide in the precursor solution in step S1 is 2:1.

[0016] It is further configured that the organic small molecule in step S1 is oleylamine.

[0017] It is further configured that the volume of the precursor solution taken in step S2 does not exceed 80 μL.

[0018] In addition, the present invention also provides a mixed cation chiral perovskite nanosheet prepared by the preparation method.

[0019] This application explores the relationship between the chiral activity and chiral molecular structure of chiral perovskites and the crystallization state of the perovskite surface. By changing the halogen atoms at the X position of the two-dimensional perovskite, perovskite nanosheets with tunable light emission, narrow emission linewidth, high quantum yield and good environmental stability can be obtained.

[0020] The innovative mechanism of the present invention is to improve the common chiral molecules (R-MBA + ) as a method for the chiral activity and circular dichroism signal of perovskite nanosheets formed by organic ammonium. This method adopts a dual ligand strategy and uses a ligand-assisted co-precipitation method to synthesize mixed cation perovskite nanosheets. This method is simple and fast, and the synthesized nanosheets have a high circular dichroism signal at a fixed ratio, and its anisotropy factor g abs =-3.8×10 -3 In view of this phenomenon, a dual ligand-assisted co-precipitation method was used to synthesize chiral perovskite nanosheets with three chiral ammonium cations with different structures, and the reason was verified by circular dichroism test results. In addition, the nanosheets obtained by this method have adjustable wavelength and good stability. The present invention can be used to design high CD value and anisotropy factor g abs Chiral perovskites provide new approaches and promote the development of chiral optical devices.

[0021] The beneficial effects of the present invention are as follows:

[0022] 1. The synthesis method of the present invention is simple and fast, and the obtained chiral perovskite nanosheet has a strong circular dichroism signal. In one embodiment of the present invention, its anisotropy factor is g abs =3.8×10 -3 , and the wavelength is tunable, which can achieve emission from blue to green, with good stability, and still maintains good fluorescence intensity after 21 days.

[0023] 2. The present invention studies the ratio of different chiral molecules and achiral molecules to explore the surface crystallization condition and morphology. The specific experimental results can explain the relationship between the crystallinity and circular dichroism signals of perovskite nanosheets. Due to the addition of achiral ammonium cations, the surface crystallinity of pure chiral perovskite nanosheets is improved, thereby improving its circular dichroism.

[0024] 3. The present invention studies chiral molecular structures and can design high CD values ​​and anisotropy factors g abs Chiral perovskites provide new approaches and promote the development of chiral optical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0026] Figure 1 The chiral perovskite nanosheet (R-MBA) in Example 1 of the present invention x PEA 1-x ) 2 PbB 4 Scanning electron micrograph of NSs);

[0027] Figure 2 The chiral perovskite nanosheet (R-MBA) in Example 1 of the present invention x PEA 1-x ) 2 PbB 4 NSs) XRD spectrum;

[0028] Figure 3 The chiral perovskite nanosheet (R-MBA) in Example 1 of the present invention x PEA 1-x ) 2 PbB 4 NSs) UV absorption spectrum (solid line) and fluorescence emission spectrum (dashed line);

[0029] Figure 4 The chiral perovskite nanosheet ((R- / S-MBA) in Example 1 of the present invention x PEA 1-x ) 2 PbB 4 (a) Circular dichroism spectrum of NSs and (b) corresponding g value trend line graph;

[0030] Figure 5The chiral perovskite nanosheet (R-MPEA) in Examples 2 and 3 of the present invention x PEA 1-x ) 2 PbB 4 NSs, (RN-DMBA x PEA 1-x ) 2 PbB 4 UV absorption spectrum and fluorescence emission spectrum of NSs), a, b are (R-MPEA x PEA 1-x ) 2 PbB 4 (a) UV absorption spectrum and (b) fluorescence emission spectrum of NSs, c, d are (RN-DMBA x PEA 1-x ) 2 PbB 4 (c) UV absorption spectrum and (d) fluorescence emission spectrum of NSs;

[0031] Figure 6 The chiral perovskite nanosheet (a) ((R-MPEA) in Examples 2 and 3 of the present invention x PEA 1-x ) 2 PbB 4 NSs, (b) (RN-DMBA x PEA 1-x ) 2 PbB 4 (a) Circular dichroism spectra of chiral perovskite nanosheets (NSs) and (c) g-value trend line graphs of chiral ammonium molecules with three different structures.

[0032] Figure 7 The chiral perovskite nanosheet (R-MBA) in Example 4 0.75 PEA 0.25 ) 2 PbB 4(1-y) I 4y NSs) (a) fluorescence emission spectrum, (b) UV absorption spectrum and (c) circular dichroism spectrum;

[0033] Figure 8 The chiral perovskite nanosheet (R-MBA) in Example 1 of the present invention 0.75 PEA 0.25 ) 2 PbB 4 The fluorescence spectrum of NSs was tested for its storage stability. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0035] In the following examples, chiral organic ammonium and achiral organic ammonium are replaced by abbreviations, specifically:

[0036] R- / S-methylbenzylammonium bromide (R- / S-MBABr), R- / S-methylphenethylammonium bromide (R- / S-MPEABr), R- / SN-methylphenethylammonium bromide (R- / SN-DMBABr), R- / S-methylbenzylammonium iodide (R- / S-MBAI).

[0037] Phenethylammonium bromide (PEABr), phenethylammonium iodide (PEAI).

[0038] Embodiment 1:

[0039] A chiral dual-ligand perovskite nanosheet (R- / S-MBA) x PEA 1-x ) 2 PbB 4 The preparation steps of the nanosheets are as follows: the raw materials for preparing the nanosheets include: the amount of several substances of R- / S-MBABr and PEABr (see Table 1), PbBr 2 (0.04mmol) and oleylamine (1.25μL) were dissolved in N,N-dimethylformamide (1mL) to prepare precursor solution 1. 20μL of precursor solution 1 was added into vigorously stirred toluene (5mL) for 2min to obtain a uniformly dispersed colloidal solution. The final solution was (R- / S-MBA x PEA 1-x ) 2 PbB 4 NSs.

[0040] The specific ratios are shown in Table 1:

[0041] x R- / S-MBABr PEABr <![CDATA[PbBr 2 ]]> 0 0 0.08mmol 0.04mmol 0.25 0.02mmol 0.06mmol 0.04mmol 0.50 0.04mmol 0.04mmol 0.04mmol 0.75 0.06mmol 0.02mmol 0.04mmol 1.00 0.08mmol 0 0.04mmol

[0042] Figure 1 and Figure 2 Given (R-MBA x PEA 1-x ) 2 PbB 4 The corresponding scanning electron microscopy and XRD spectra of NSs are shown in Figure 2. Figure 1 and Figure 2 It can be seen that the prepared product exhibits the characteristics of perovskite nanosheets.

[0043] Embodiment 2:

[0044] A chiral dual-ligand perovskite nanosheet (R-MPEA x PEA 1-x ) 2 PbB 4 NSs) were prepared as follows: the amounts of several substances of R-MPEABr and PEABr (see Table 2), PbBr 2 (0.04mmol) and oleylamine (1.25μL) were dissolved in N,N-dimethylformamide (1mL) to prepare precursor solution 2. 20μL of precursor solution 2 was added to vigorously stirred toluene (5mL) for 2min to obtain a uniformly dispersed colloidal solution. The final solution was (R-MPEA x PEA 1-x ) 2 PbB 4 NSs.

[0045] The specific proportions are shown in Table 2:

[0046] x R-MPEABr PEABr <![CDATA[PbBr 2 ]]> 0 0 0.08mmol 0.04mmol 0.25 0.02mmol 0.06mmol 0.04mmol 0.50 0.04mmol 0.04mmol 0.04mmol 0.75 0.06mmol 0.02mmol 0.04mmol 1.00 0.08mmol 0 0.04mmol

[0047] Embodiment 3:

[0048] A chiral dual-ligand perovskite nanosheet (RN-DMBA) x PEA 1-x ) 2 PbB 4 NSs) was prepared as follows: the amount of RN-DMBABr and PEABr (see Table 3), lead bromide (0.04 mmol) and oleylamine (1.25 μL) were dissolved in N,N-dimethylformamide (1 mL) to prepare precursor solution 3, 20 μL of precursor solution 3 was added to vigorously stirred toluene (5 mL) for 2 min to obtain a uniformly dispersed colloidal solution. The final solution was (RN-DMBA x PEA 1-x ) 2 PbB 4 NSs.

[0049] The specific proportions are shown in Table 3:

[0050] x RN-DMBABr PEABr <![CDATA[PbBr 2 ]]> 0 0 0.08mmol 0.04mmol 0.25 0.02mmol 0.06mmol 0.04mmol 0.50 0.04mmol 0.04mmol 0.04mmol 0.75 0.06mmol 0.02mmol 0.04mmol 1.00 0.08mmol 0 0.04mmol

[0051] Embodiment 4:

[0052] A series of chiral ammoniums emitting at different wavelengths were synthesized into dual-ligand perovskite nanosheets (R-MBA) using a dual-ligand strategy. 0.75 PEA 0.25 ) 2 PbB 4(1-y) I 4yNSs) are prepared in the following steps: R-MBABr, PEABr, R-MBAI, PEAI, PbBr 2 、PbI 2 The amount of each of the several substances (see Table 4) and oleylamine (1.25 μL) were dissolved in N, N-dimethylformamide (1 mL) to prepare precursor solution 4. 20 μL of precursor solution 4 was added to vigorously stirred toluene (5 mL) for 2 min to obtain a uniformly dispersed colloidal solution. The final solution was (R-MBA 0.75 PEA 0.25 ) 2 PbB 4(1-y) I 4y NSs.

[0053] The specific proportions are shown in Table 4:

[0054]

[0055]

[0056] In order to further verify the optical properties of the prepared chiral perovskite nanosheets, the present invention conducted emission spectrum tests and circular dichroism spectrum tests on the products obtained in typical examples 1, 2 and 3, respectively. The details are as follows:

[0057] (I) Testing the emission spectrum of the prepared chiral perovskite nanosheets

[0058] 1. Emission spectrum test of chiral molecular perovskite nanosheets with different structures:

[0059] Samples used: (R- / S-MBA prepared in typical examples 1, 2 and 3 x PEA 1-x ) 2 PbB 4 NSs, (R-MPEA x PEA 1-x ) 2 PbB 4 NSs, (RN-DMBA x PEA 1-x ) 2 PbB 4 NSs.

[0060] Instrument used: Hitachi fluorescence detector 5J1-0004.

[0061] Test steps: put the sample into a quartz cuvette with four sides transparent to light, open the lid of the instrument, put the cuvette into the bracket and cover it, then open the spectrum test software on the computer, select the xenon lamp as the light source and set the excitation light wavelength to 365nm, finally select the appropriate slit by adjusting the size of the slit, select the emission spectrum wavelength range of 380 600nm on the test interface, and click Start; save the data after testing a sample; test the next sample according to the above steps. Finally, adjust the slit to the minimum, then take out the cuvette, pour out the sample, wash it with ethanol, and put it in the box.

[0062] Test results: Under 365nm excitation light, the luminescence spectrum of the chiral perovskite nanosheets prepared in Example 1, Example 2 and Example 3 is 405-415nm, which is a purple emission spectrum. Figure 3 and Figure 5 .

[0063] 2. Emission spectrum test of chiral perovskite nanosheets emitting at different wavelengths

[0064] Sample used: (R-MBA prepared in Typical Example 4 0.75 PEA 0.25 ) 2 PbB 4(1-y) I 4y NSs.

[0065] Instrument used: Instrument used: Hitachi fluorescence detector 5J1-0004.

[0066] Test steps: put the sample into a quartz cuvette with four sides transparent to light, open the lid of the instrument, put the cuvette into the bracket and cover it, then open the spectrum test software on the computer, select the xenon lamp as the light source and set the excitation light wavelength to 365nm, finally select the appropriate slit by adjusting the size of the slit, select the emission spectrum wavelength range of 380 700nm on the test interface, and click Start; save the data after testing a sample; test the next sample according to the above steps. Finally, adjust the slit to the minimum, then take out the cuvette, pour out the sample, wash it with ethanol, and put it in the box.

[0067] Test results: Under 365nm excitation light, the luminescence spectrum of the chiral perovskite nanosheet prepared in Example 4 is 400-530nm nm, which is a purple-green emission spectrum. Figure 7 .

[0068] 3. Emission spectrum storage stability test of chiral perovskite nanosheets

[0069] Sample used: (R-MBA prepared in Typical Example 1 0.75 PEA 0.25 )2 PbB 4 NSs.

[0070] Instrument used: Instrument used: Hitachi fluorescence detector 5J1-0004.

[0071] Test steps: Place the sample in a quartz cuvette that is transparent on all sides, open the lid of the instrument, place the cuvette in the bracket and cover it, then open the spectrum test software on the computer, select a xenon lamp as the light source and set the excitation light wavelength to 365nm, finally select a suitable slit by adjusting the size of the slit, select the emission spectrum wavelength range of 380-700nm on the test interface, and click Start; save the data after testing a sample; test the sample again according to the above steps at regular intervals until the test is stopped after 21 days. After the last test, adjust the slit to the minimum, then take out the cuvette, pour out the sample, wash it with ethanol, and put it in the box.

[0072] Test results: Under 365nm excitation light, (R-MBA prepared in Example 1 0.75 PEA 0.25 ) 2 PbB 4 NSs have good stability. After 21 days, the fluorescence intensity only decreased by about 10%. Figure 8 .

[0073] (II) Testing the circular dichroism and ultraviolet absorption spectra of the prepared chiral perovskite nanosheets

[0074] Samples used: A series of chiral perovskite nanosheets prepared in typical examples 1, 2, 3 and 4

[0075] Instrument used: Applied Photophysics Chirascan

[0076] Test steps: Turn on the instrument and preheat it with nitrogen for 15 minutes. Scan the air sample first, then deduct the background, put the solvent toluene into the micro quartz cuvette with two transparent sides, open the lid of the instrument, align the two transparent sides of the cuvette with the incident light and the detector respectively, and then put it into the bracket, cover the instrument cover and set it on the computer operation page, select the test range of 200 800nm, the scanning speed of 0.6nm / s, click the start button, take it out after the end, and save the data; then put the test sample in, cover the instrument cover, click to start the test on the computer page, and the CD spectrum and ultraviolet absorption spectrum will be scanned out at the same time. Save the data after the test and manually deduct the background. Then take out the cuvette, pour out the sample and wash it with ethanol, rinse it with toluene, and then put in the next sample to continue the above test operation. After the last sample is tested, turn off the instrument and continue to pass nitrogen for 10 minutes before turning off the gas.

[0077] Test results: The above test results show that the absorption spectra of a series of chiral perovskite nanosheets prepared by the present invention have the same evolution law as the corresponding emission spectra, and also have chiral signals. In addition, the circular dichroism spectra of perovskite nanosheets prepared by R MBABr and SMBABr are symmetrical, indicating that their chirality is transferred to the perovskite material, and the g value can reach up to 3.8×10 -3 By changing the structure of the chiral molecule, the relationship between the chiral ammonium cation structure and the circular dichroism signal can be clearly found, and by adjusting the halogen, the peak position of the circular dichroism spectrum can be found to move accordingly. Figure 3 , Figure 5 and Figure 7 , circular dichroism spectrum see Figure 4 , Figure 6 and Figure 7 .

[0078] The present invention adopts a ligand-assisted co-precipitation method, which is simple and easy to implement. The synthesized nanosheet has an excellent circular dichroism signal, and the influence of its surface crystallization state on the circular dichroism signal can be obtained by analyzing the ratio of its chirality and non-chiral cations. And by comparing the circular dichroism signals of the double-ligand perovskite nanosheets formed by three different chiral ammonium cations, the relationship between its circular dichroism signal and structure is clearly found, and the influence of the surface crystallization state on the circular dichroism signal that cannot be ignored is further verified. And through this method, a series of chiral perovskite nanosheets with circular dichroism response and tunable wavelength can be conveniently obtained. Because it has an obvious chiral signal, it can be widely used in the fields of photodetectors, polarization optical devices, etc.

[0079] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing mixed cation chiral perovskite nanosheets, characterized in that The preparation method comprises the following steps: S1: Chiral organic ammonium, achiral organic ammonium and lead halide are used as perovskite precursors, organic small molecules are used as surface ligands, and N, N'-dimethylformamide is used as solvent to form a precursor solution; S2: using toluene as an anti-solvent, adding the precursor solution prepared in step S1 into the anti-solvent to synthesize mixed cation chiral perovskite nanosheets; The chiral organic ammonium is R - / S -Methylbenzylammonium bromide, R - / S -Methylphenethylammonium bromide, R - / S -N-Methylphenethylammonium bromide, R - / S -Methylbenzylammonium iodide; The achiral organic ammonium in step S1 is any one of phenethylammonium bromide and phenethylammonium iodide; the lead halide in step S1 is PbBr2 or PbI2; and the organic small molecule in step S1 is oleylamine.

2. The method for preparing the mixed cation chiral perovskite nanosheet according to claim 1, characterized in that: The total amount of the mixed ammonium salts in step S1 remains unchanged.

3. The method for preparing mixed cation chiral perovskite nanosheets according to claim 1, characterized in that: The total amount of the mixed lead salts in step S1 remains unchanged.

4. The method for preparing mixed cation chiral perovskite nanosheets according to claim 1, characterized in that: The molar ratio of the mixed organic ammonium cation and the lead halide in the precursor solution in step S1 is 2:

1.

5. The method for preparing mixed cation chiral perovskite nanosheets according to claim 1, characterized in that: The volume of the precursor solution taken in step S2 does not exceed 80 µL.

6. A mixed cation chiral perovskite nanosheet prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Chiral perovskite nanosheet and preparation method and application thereof

    CN111362809A

  • Method of forming a crystalline or polycrystalline layer of an organic-inorganic metal halide perovskite

    CN112840473A

Cited By

  • Self-assembled heterogeneous chiral perovskite thin film, preparation method thereof and perovskite thin film transistor

    CN121665876A